Manajemen Kolaborasi Pemangku Kepentingan Dalam Pengelolaan Wilayah Perbatasan Pada PBLN Sota Kabupaten Merauke - Tambajong, Hesty; Oja, Hubertus; Moento, Paul; Meisaroh, Yuyun (SOCIETAS, 2024)
Border areas are the front porch of the State, because border areas are areas that face other countries. In South Papua Province, specifically Sota District, which is a district that borders directly with the country of Papua New Guinea. Stakeholder collaborative management is important in managing border areas, especially in areas that have various dynamics such as the Sota State Cross Border Post (PLBN) in Merauke Regency. This research aims to analyze collaboration between various stakeholders in the management of PLBN Sota. This research uses qualitative methods to analyze data obtained through interviews, observation, documentation and literature study. The research results show that in the border area of ​​Sota District there are problems such as unauthorized border crossers, fuel smuggling, and also marijuana plant smuggling which require collaboration between stakeholders to minimize illegal actions.